Unlocking the potential of justice-impacted talent : getting intentional about second-chance hiring can lead to a more diverse workforce and promote economic growth during a time of labor shortages - Cumming, Ben (MIT Sloan Management Review, 2023)
Having a criminal record can be a major barrier to employment. When companies implement programs and policies that support the hiring of justice-impacted talent, including the formerly incarcerated, both they and the affected individuals stand to benefit. The author describes some of the efforts underway by nonprofit organizations and major employers to tap into this underutilized talent pool and provide people with a second chance to thrive in today’s workforce.